2003
DOI: 10.1016/s0741-5214(03)00315-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety of gadolinium contrast angiography in patients with chronic renal insufficiency

Abstract: Despite reports of negligible nephrotoxicity, rarely gadolinium-based contrast agents can cause acute renal failure in patients with underlying chronic renal insufficiency. Estimation of creatinine clearance alone does not enable prediction of which patients are likely to have acute renal failure. Patients at high-risk should be identified, and prophylactic measures should be taken to reduce the risk for nephrotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
102
0
4

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(108 citation statements)
references
References 20 publications
1
102
0
4
Order By: Relevance
“…Recent reports have suggested that gadolinium-based contrast agents may lead to acute renal failure in patients with advanced renal disease (22,23). We also routinely obtain images through the abdomen with steady-state free-precession gradient echo and fat-saturated T2-weighted spin echo sequences before gadolinium administration.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Recent reports have suggested that gadolinium-based contrast agents may lead to acute renal failure in patients with advanced renal disease (22,23). We also routinely obtain images through the abdomen with steady-state free-precession gradient echo and fat-saturated T2-weighted spin echo sequences before gadolinium administration.…”
Section: Study Limitationsmentioning
confidence: 99%
“…However, the two CM were compared at an extremely different x-ray attenuation capacity. Thus the "off-label" recommendation to use Gd-CM as a safer alternative than I-CM in azotemic patients in a variety of XRA examinations-including aortofemoral (12,13), renal (14 -17), carotid (18), and coronary arteriography (19,20)-is, in our opinion, based on an incorrect comparison. The only reason for using I-CM or Gd-CM in XRA is to exploit their ability to attenuate x-rays.…”
mentioning
confidence: 98%
“…In our experience, abscesses are also clearly demonstrated on STIR sequences, but if there is difficulty distinguishing phlegmon from abscess, then contrast is used. We prefer to use contrast only in select cases because of the added cost, the increased time necessary to inject and obtain additional sequences, and because of concerns for nephrotoxicity and nephrogenic systemic fibrosis in patients with renal insufficiency [21,23].…”
Section: Discussionmentioning
confidence: 99%